Pursuing my Dream: Becoming a PhD in Linguistics - Davronbekova Dilnoza Dilshojon qizi (Лучшие интеллектуальные исследования, 2024)
Annotation: This article explores the aspirations and journey of a 9th-grade student, Davronbekova Dilnoza, towards achieving a PhD in Linguistics. It delves into her motivations, challenges, and the steps she plans to take to fulfill her dream. Through her perspective, readers gain insights into the passion and determination required to pursue an advanced academic path from a young age.